Rural depopulation policies in Sweden: What can rural municipalities do to reverse a population decline? - Larsson,Per (2014)
There is an urbanization process going on all over the world and even if the process has a slower pace in Sweden now than during the industrialization period, the rural areas has experienced a general population decline the last two decades, despite a population growth nationally. This population decline has negative consequences for the Swedish rural municipalities and most of them uses, beside their mandatory welfare duties, various policies aimed towards having a positive population development. This study uses two different methods with one large N study and one small N study of rural municipalities with the intention of increase our understanding on how municipalities work to counter depopulation and what policies that actually have an impact on population changes, and whether or not these can be regarded as effective. The results show that municipalities work differently towards population changes and it is hard to make any conclusions about the effectiveness of the policies used. The conclusion is made that all municipalities face different prerequisites and there is no ‘one size fit all’ solution, and hence municipalities should focus on being as good as possible in their welfare duties.
Keywords: Sweden; rural municipalities; rural depopulation; municipal policies